The Effectiveness of Blended Learning During the Covid-19 Pandemic at the High School Level - Tengku Mohd Khairal Abd; Badi Atussolihah; Fransisca Dania Prima Kasillia; Dilla Swaestya (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to determine the effectiveness of the application of blended learning on student motivation, student characteristics, and student interaction. The method used in this study is comparative quantitative by comparing the final grades of students before and during the covid-19 pandemic as supporting data. The population in this study were all students of classes XI and XII with a total sample of 218 students with a sample of 160 students taken using purposive sampling. Furthermore, the data collection technique was carried out by distributing questionnaires using google form media. And analyzed using content analysis. The results showed that there was a significant difference in students' final grades as evidence of the effectiveness of applying blended learning compared to face-to-face classes for mathematics, English, and Indonesian subjects; There is no significance between student characteristics and the effectiveness of blended learning; No significance between student interaction and the effectiveness of blended learning; There is a significance between learning motivation and the effectiveness of blended learning.